POTENTIAL DEMAND FOR AGRICULTURAL THE SCOPE OF AGRICULTURAL ECONOMICS AND ECONOMISTS IN LIBYA - A. Afifi, Hani (The Libyan Journal of Agriculture, 2023)
Agricultural economists are needed in Libya to find answers to ihe following questions : 1 >Is it economically feasible to desalinate water for irrigation in Libya? 2) Are the cooperatives improving the marketing and production efficency of Libyan agricultural products ? 3) What i3 the efficient approach to manage the required farms from Italians ? Related questions are : a) How to evaluate the existing enterprises ? b) How to increase the agricultural land within the given funds at hard ? c) How to improve agricultural production ? 4) How to make an economic plan for importing and exporting agricultural products in Libya ? 5) Are the farm subsidies from Ministry of agriculture and loans from Agricultural Bank improving Libyan agricultural products ? 6) Does Libya has proper marketing facilities such as paved roads, refrigerated trucks, storage rooms, and processing plants ? Are the processing plan s operating efficiently or not Does Libya need more or less of these plants ? Are the prosishable products ( milk, tomatoe, etc ) located with easy access to the markets ? 7) What is the economic impact of rural migration on agricultural production in Libya ? 8) What are the cost and benefits of using farm machinery in Libya ? 9) What is the optimum use of land and water resources in Libya ? ( fishing, swimming, camping, golfing, etc ).